2008
DOI: 10.1021/jm800338j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Peripheral Serotonin Levels by Novel Tryptophan Hydroxylase Inhibitors for the Potential Treatment of Functional Gastrointestinal Disorders

Abstract: The discovery of a novel class of peripheral tryptophan hydroxylase (TPH) inhibitors is described. This class of TPH inhibitors exhibits excellent potency in in vitro biochemical and cell-based assays, and it selectively reduces serotonin levels in the murine intestine after oral administration without affecting levels in the brain. These TPH1 inhibitors may provide novel treatments for gastrointestinal disorders associated with dysregulation of the serotonergic system, such as chemotherapy-induced emesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 18 publications
1
41
0
1
Order By: Relevance
“…A breakthrough in pharmacologic inhibition of TPH was achieved with the discovery of molecules whose expanded pCPA core gained selectivity over related amino acid hydroxylases (phenylalanine and TH). Selectivity over TPH2 was effectively achieved through restricted distribution to the gut, including exclusion of enteric nerves (Shi et al, 2008; Margolis et al, 2014), providing both pre-clinical and clinical evidence for promising therapeutic options for gut-related disorders such as non-constipating irritable bowel syndrome (Brown et al, 2011; Kim et al, 2015). However, diseases in which pathogenesis is driven by TPH1 over expression, and subsequent 5-HT production, in peripheral tissues remain beyond the reach of these next generation inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A breakthrough in pharmacologic inhibition of TPH was achieved with the discovery of molecules whose expanded pCPA core gained selectivity over related amino acid hydroxylases (phenylalanine and TH). Selectivity over TPH2 was effectively achieved through restricted distribution to the gut, including exclusion of enteric nerves (Shi et al, 2008; Margolis et al, 2014), providing both pre-clinical and clinical evidence for promising therapeutic options for gut-related disorders such as non-constipating irritable bowel syndrome (Brown et al, 2011; Kim et al, 2015). However, diseases in which pathogenesis is driven by TPH1 over expression, and subsequent 5-HT production, in peripheral tissues remain beyond the reach of these next generation inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…More recent molecules such as Telotristat etiprate, which more potently inhibits TPH1/2 than pCPA, with better selectivity over related aromatic amino acid hydroxylases, have demonstrated efficacy in carcinoid syndrome trials showing some symptomatic improvements and good tolerability (Kulke et al, 2014). The distribution and activity of telotristat etiprate is predominantly gut restricted (Shi et al, 2008; Kim et al, 2015) - the principal site of physiologic TPH1 activity/5-HT production – avoiding the adverse effects of TPH2-mediated 5-HT production in the CNS and consequent psychiatric toxicity. However, the efficacy of such a therapeutic strategy is limited in diseases where the principal site of pathologic 5-HT production is distal to the gut, such as pulmonary endothelium in PAH or lung metastases in carcinoid syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Whether targeting of 5-HT signaling can also be developed as an intervention for bone, without compromise to other 5-HT sensitive systems, will be determined with further work. One starting point may be the investigation of orally-active, peripheral-specific inhibitors of Tph1 [59, 60]. These agents selectively inhibit 5-HT synthesis in the periphery as they are unable to cross the blood-brain barrier and, based on the work of Yadav et al [4], should be potently anabolic within the skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…23 Medicinal chemistry and preclinical pharmacology data for these TPH inhibitors have been published. [24][25][26][27] A limitation of this report is the lack of mechanistic studies designed to explain the observed trabecular and cortical bone phenotypes in Tph2 KO mice. High trabecular bone BV/TV resulting from elevated trabecular number rather than greater trabecular thickness is consistent with reduced bone resorption rather than increased bone formation.…”
Section: Discussionmentioning
confidence: 99%